SPECT/CT in the Diagnosis of Skull Base Osteomyelitis - Damle, Nishikant Avinash (Springer-Verlag, 2011)
Skull base osteomyelitis is a potentially fatal disease. We demonstrate here the utility of SPECT/CT in diagnosing this entity, which was not obvious on a planar bone scan. A (99m)Tc MDP bone scan with SPECT/CT was carried out on a patient with clinically suspected skull base osteomyelitis. Findings were correlated with contrast-enhanced CT (CECT) and MRI. Planar images were equivocal, but SPECT/CT showed intense uptake in the body of sphenoid and petrous temporal bone as well as the atlas corresponding to irregular bone destruction on CT and MRI. These findings indicate that SPECT/CT may have an additional role beyond planar imaging in the detection of skull base osteomyelitis.